Identification of miRNAs and their potential effects on multiple sclerosis related pathways using in silico analysis - Erkal, Burcin; Korkut, Senay Vural (ELSEVIER SCI LTD, 2022)
Background: MicroRNAs (miRNAs) regulate gene expression post-transcriptionally via mRNA degradation. As a result, they have an impact on a variety of pathways in organisms that are important for both health and disease. miRNAs can be used as potential diagnostic, prognostic and therapeutic biomarkers for immune and nervous system-related diseases such as MS.Method: Differentially expressed miRNAs from peripheral blood samples of patient and control groups were selected from NCBI GEO Datasets using GEO2R. Common miRNAs and their related pathways were analyzed using miRNet, miRWalk, DIANA mirpath, KEGG pathway. Target genes and their protein-protein interactions were also evaluated using STRING and GeneMANIA.Results: We found 12 common miRNAs, four of which were determined to be more important in MS-related pathways such as the immune and neural signaling networks. These include pathways neurotrophin, JAK -STAT, B cell receptor, ErbB, MAPK, Fc gamma R-mediated phagocytosis, Chemokine and T cell receptor signaling pathways. Moreover, target gene analyses were performed and MAPK1, PIK3CD, PIK3R1, PIK3R2, PIK3R3, PIK3R5, AKT2, SOS2, RAF1 genes were found. Further analysis showed that the identified genes and related pathways have interactions at multiple points, and that the overlapping points are commonly found in the PI3K-Akt signaling pathway.Conclusion: In this paper, MS-related miRNAs and their potential effects on related pathways were evaluated. This study can be used for understanding MS pathogenesis and provides new tools for the discovery of new therapies.
Keywords: Multiple Sclerosis; In silico analysis; Biomarker; miRNA; EXPRESSION; MICRORNAS; Neurosciences & Neurology